2015
DOI: 10.1002/jmri.25112
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted imaging and 18F‐fluorodeoxyglucose positron emission tomography/computed tomography in breast cancer: Correlation of the apparent diffusion coefficient and maximum standardized uptake values with prognostic factors

Abstract: SUVmax may be valuable for predicting the prognosis of breast cancer. Both ADC and SUVmax are useful to predict vascular invasion. J. Magn. Reson. Imaging 2016;43:1434-1444.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 40 publications
7
31
0
Order By: Relevance
“…In a sample of 70 breast cancer patients, Karan et al found that the median ADC value was significantly associated with vascular invasion (P=0.008). The maximum SUV (SUVmax) was also significantly correlated with tumour size (P=0.001), histological grade (P=0.001), lymph node status (P=0.0015), oestrogen receptor status (P=0.010), and human epidermal growth factor receptor 2 status (P=0.020) (26). With a similar purpose, Molinari et al observed that lower ADC values are associated with elevated Ki67 proliferation index in 115 breast cancer lesions (27).…”
Section: Mri and Other Imaging Modalitiesmentioning
confidence: 88%
“…In a sample of 70 breast cancer patients, Karan et al found that the median ADC value was significantly associated with vascular invasion (P=0.008). The maximum SUV (SUVmax) was also significantly correlated with tumour size (P=0.001), histological grade (P=0.001), lymph node status (P=0.0015), oestrogen receptor status (P=0.010), and human epidermal growth factor receptor 2 status (P=0.020) (26). With a similar purpose, Molinari et al observed that lower ADC values are associated with elevated Ki67 proliferation index in 115 breast cancer lesions (27).…”
Section: Mri and Other Imaging Modalitiesmentioning
confidence: 88%
“…Our segmentation method segments the MR functional volume of lesions on the ADC map ( V ADC ) which, in BC, is directly correlated to the PET metabolic volume MTV. Regarding MR, most works have assessed the role of ADC as surrogate biomarkers for characterization and treatment response prediction [39]. To our knowledge, only one study has proposed and validated a methodology to segment ADC maps and to obtain volume-like ADC parameters as candidate biomarkers for diagnosis and prognosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the relationship between SUV and ADC have produced conflicting results [4, 39, 45]. When a negative correlation between these two parameters was found, it was suggested as highlighting the biological relationship between glucose metabolism and diffusion within a lesion [45].…”
Section: Discussionmentioning
confidence: 99%
“…Similar combined [ 18 F]FDG/ADC approaches showed high diagnostic value, for example, in lung and breast cancer patients (51,52) but could not provide prognostic thresholds due to the exclusive use of single value analysis in the breast cancer study and high grades of heterogeneity in the investigated lung disease, although analyzed by a GMM approach.…”
Section: Discussionmentioning
confidence: 99%